Investigating range error compensation in UHF radar through IRI-2007 real-time updating: Preliminary results. Issue 5 (1st September 2015) - Ovodenko, V.B.; Trekin, V.V.; Korenkova, N.A.; Klimenko, M.V.
Abstract The study of compensation radar range errors is presented. We have used a model for calculating atmospheric effects on the UHF space surveillance radar for using in near real-time. The highly precise data of calibration satellites and UHF radar measurements are used for range error calculation. We have studied four types of errors distribution. The first type corresponds to errors obtained without applying corrections. The second is obtained with applying corrections that are calculated using non-updated IRI-2007. The third and fourth types correspond to the updated IRI-2007 with slant TEC (in near real-time) and hourly foF2 respectively. The experimental results presented in this paper show that applying corrections calculated with non-updated IRI-2007 significantly reduce range error. The best result is achieved by using updated IRI-2007 equally with slant TEC and foF2.